If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+19x-7=6(4x+3)
We simplify the equation to the form, which is simple to understand
5x+19x-7=6(4x+3)
Reorder the terms in parentheses
5x+19x-7=+(+24x+18)
Remove unnecessary parentheses
+5x+19x-7=+24x+18
We move all terms containing x to the left and all other terms to the right.
+5x+19x-24x=+18+7
We simplify left and right side of the equation.
0x=+25
0=25
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x | | 4x+26x-9=6(5x+5) | | 3x-6=40 | | 3x-6+2x-4=30 | | 5x-40=8x+11 | | 28-4x=13-9x | | -161+8x=2x+99 | | 12x+15=5x+7 | | (x-1)+(x-1)=g | | y-2=(22-y)^(1/2) | | -114-2x=210+7x | | (x^2)-2x-2.5=0 | | 3a-27=54+9a | | 3x-22=13+4x | | -14+10x=11x+13 | | 5(x-2)=80-5x | | 5x-3=67-9x | | g(x)=-log^2(x-3)+1 | | -91+3x=-x+37 | | g(x)=-log^2(x-3) | | 8x+1=7-20 | | 2/3(15)=10 | | -(X^2-8X-9)=0 | | 7x+9=x+11 | | 5/y-3/4 |